2020
DOI: 10.3389/fpubh.2020.00037
|View full text |Cite
|
Sign up to set email alerts
|

Food Acquisition in the Geography of Brazilian Obesity

Abstract: Overweight and obesity are a worldwide pandemic with geographic differences. Possible explanations include variable access to food and its quality, dietary habits of the populations, behavioral patterns, and characteristics of the food markets. This study aimed to examine the acquisition of food in the different regions of Brazil and to relate it with the geography of Brazilian obesity. We used data provided by a Brazilian official organ, which gathers periodic data on the household food acquisition. Descripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Likewise physical activity, the eating habits of a population can partially justify excess weight 29 . Thus, understanding the diet characteristics can be an important instrument in public health care 29 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise physical activity, the eating habits of a population can partially justify excess weight 29 . Thus, understanding the diet characteristics can be an important instrument in public health care 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Likewise physical activity, the eating habits of a population can partially justify excess weight 29 . Thus, understanding the diet characteristics can be an important instrument in public health care 29 . The lifestyle particularities of people living in the region of Passo do Lontra may impact the free time available for meals and even the number of meals eaten per day; many individuals spend all day outside their homes working in the river or in the Pantanal wetlands 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study showed that females, with lower education and incomes, have higher overweight and obesity levels in Brazil. There is an association between unhealthy food intake and poverty [ 37 ]. The ability to be a competent eater is affected by food insecurity and/or income restrictions, as having worries about money for food is associated with a lack of EC [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in total cholesterol and fractions are strongly associated with acute myocardial infarction, peripheral arterial disease and stroke . Obesity is an independent risk factor and increases the risk of SAH, T2DM and dyslipidemia (ALVES et al, 2020). In addition, lean mass loss is related to reduced mobility and autonomy in activities of daily living (NERI et al, 2020).…”
Section: Introductionmentioning
confidence: 99%